Analysis of Student Needs for the Development of Arabic Language Teaching Materials at Madrasah Ibtidaiyyah Al Birru Ponorogo - Nuraini, Nuraini; Arifin, Syamsul; Rahmawati, Ida Yeni; Tajab, Muh. (Postgraduate Program Magister Pendidikan Agama Islam, 2023)
Arabic is a foreign language which is a compulsory subject in Madrasas, therefore learning Arabic is a superior program in madrasas which differentiates it from other public schools. Arabic language learning in Indonesia in particular is currently experiencing an increase, various innovations are starting to be made, one of which is developing teaching materials according to the needs of madrasa students. Developing teaching materials seems to be something that teachers must do in order to attract students' interest in learning Arabic. Some textbooks that are often used by schools are basically textbooks that originate from the Middle East. Even though there has been textbook development carried out by Arabic language teachers and developers, there are still very few who pay attention to students' needs in learning Arabic. The research will begin with coordination and interviews with the school principal to find out Arabic language learning achievements, who will then conduct interviews with teachers and students regarding their tendencies to learn Arabic, students' backgrounds and observations of the Arabic language learning tools used. Next, carry out a needs analysis as a basic material for developing Arabic teaching materials for Madrasah Al Birru Ponorogo students. The output of the research is in the form of scientific articles which will be published in reputable journals in the field of Arabic language education such as Al-Bayan, and so on.